Towards an operational measurement of socio-ecological performance - Claudia Kettner; Angela Köppl; Sigrid Stagl (WWWforEurope, 2014)
Questioning GDP as dominant indicator for economic performance has become commonplace. For economists economic policy always aims for a broader array of goals (like income, employment, price stability, trade balance) alongside income, with income being the priority objective. The Stiglitz-Sen- Fitoussi Commission argued for extending and adapting key variables of macroeconomic analysis. International organisations such as the EC, OECD, Eurostat and UN have proposed extended arrays of macroeconomic indicators (see `Beyond GDP', `Compendium of wellbeing indicators', `GDP and Beyond', 'Green Economy', 'Green Growth', 'Measuring Progress of Societies'). Despite these high profile efforts, few wellbeing and environmental variables are in use in macroeconomic models. The reasons for the low uptake of socio-ecological indicators in macroeconomic models range from path dependencies in modelling, technical limitations, indicator lists being long and unworkable, choices of indicators appearing ad hoc and poor data availability. In this paper we review key approaches and identify a limited list of candidate variables and – as much as possible – offer data sources.
Keywords: D6; 330; Academic research; Beyond GDP; Biophysical constraints; Ecological integrity; Economic growth path; Socio-ecological transition; Wealth; Wellbeing